2009
DOI: 10.1063/1.3116082
|View full text |Cite
|
Sign up to set email alerts
|

Can a double stranded DNA be unzipped by pulling a single strand?: Phases of adsorbed DNA

Abstract: We study the unzipping of a double stranded DNA (dsDNA) by applying an external force on a single strand while leaving the other strand free. We find that the dsDNA can be unzipped to two single strands if the external force exceeds a critical value. We obtain the phase diagram which is found to be different from the phase diagram of unzipping by pulling both the strands in opposite directions. In the presence of an attractive surface near DNA, the phase diagram gets modified drastically and shows richer surpr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
16
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 46 publications
1
16
0
Order By: Relevance
“…It is known from various theoretical models that, for both melting and unzipping, the nature of the transition depends on the aspects of the DNA captured in a model [2,7,[10][11][12][13][14][15][16][17][18][19][20]. Any natural DNA, because of its large length, is expected to show the characteristic features of the transitions; however, the situation is not so clear on the experimental front.…”
Section: Introductionmentioning
confidence: 99%
“…It is known from various theoretical models that, for both melting and unzipping, the nature of the transition depends on the aspects of the DNA captured in a model [2,7,[10][11][12][13][14][15][16][17][18][19][20]. Any natural DNA, because of its large length, is expected to show the characteristic features of the transitions; however, the situation is not so clear on the experimental front.…”
Section: Introductionmentioning
confidence: 99%
“…In the last two decades there have been several in vitro experimental studies (see [2][3][4][5][6][7] and references therein) on unzipping transitions due to the development of single molecule manipulation techniques such as atomic force microscopy, optical and magnetic tweezers, etc. These studies have been supplemented by theoretical modeling [8][9][10][11][12][13][14][15][16][17][18][19] which have provided useful insights into the problem including the unzipping phase diagram 12,13 . It was found that the unzipping of a dsDNA is a first order phase transition implying that the DNA remains in a zipped phase unless the force that pulls apart its strands exceeds a critical value 8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…A double-stranded (ds) DNA remains in the bound doublet state below its melting temperature even when pulled by a force at one end until and unless the force exceeds a critical force g = g c (T ), above which it opens into two single stranded (ss) DNA. Many aspects of this transition have been studied since then both theoretically [6][7][8][9][10][11][12][13][14][15] and experimentally [4,16,17], mostly in equilibrium, though puzzles remain [18,19].In vivo, a DNA is opened by helicases, which are motors that move along the DNA[1]. Both the motion and the opening processes require constant supply of energy.A few examples are DNA-B, a ring like hexameric helicase that pushes through the DNA like a wedge [20], PcrA that goes through cycles of pulling the ds part of the DNA and then moving on the ss part [21], viral RNA helicase NPH-II that hops cyclically from the ds to the ss part of DNA and back [22].…”
mentioning
confidence: 99%